Surgical outcome of COVID-19 infected patients: experience in a tertiary care hospital in India - Singh, Charan; Kaman, Lileswar; Shah, Aruj; Thakur, Uttam Kumar; Ramavath, Krishna; Jaideep, B.; Tandup, Cherring; Savlania, Ajay; Kajal, Kamal; Behera, Arunanshu (International Surgery Journal, 2021)
Background: COVID-19 disease caused by SARS-COV-2 has become a pandemic. Outcome of surgical patients infected with COVID-19 is not very clear. Methods: Retrospective analysis of the surgical outcome of COVID-19 infected patients admitted in emergency and elective surgical settings in a designated COVID care center. Results: Total 53 patients were included. Surgery was done in 47.16% (n=25) patients and 52.84% (n=28) patients were managed non-operatively. Overall mortality was 37.7 % (n=20). In operated group it was 52% (n=13) and 25% (n=7) in the non-operative group (p=0.043). The total leukocyte (p=0.018), serum CRP (p=0.031), urea and creatinine level (p=0.025) were higher in the mortality group. Patients aged more than 50 years had a significantly higher mortality compared to less than 50 years (p=0.010). Patients having multiple comorbidities had higher mortality (p=0.159). Conclusions: COVID-19 infection has a definite adverse impact on the outcomes of surgical patients.